Making biotech a driving force - Abd Razak, Dzulkifli (2005)
With the announcement of the National Biotechnology Policy by the Prime Minister at the opening of BioMalaysia 2005 recently, another "buzzword" has been introduced to the Malaysian community. A few years ago, it was IT and ICT with the MSC (the Multimedia Super Corridor). Now it's BioValley and BioNexus. What do we make of these? Let us backtrack to just over three decades, when a bio chemist from the University of California in San Francisco and a geneticist from Stanford perfected a technique for inserting a toad's DNA into a bacterium. The socalled newlycreated lifeform not only lived but also reproduced. It soon inspired the founding of a startup called Genentech.